THE INFLUENCES OF SELF-EFFICACY AND READING INTEREST TOWARD READING ACHIEVEMENT OF THE EIGHTH GRADE STUDENTS OF STATE SCHOOL IN BATURAJA TIMUR SUBDISTRICT. PALEMBANG: - Nurul Afifah (ELTE Journal (English Languange Teaching and Education), 2016)
ABSTRACTThis study aimed at finding out whether or not: (1) there is a significant influence between Self-efficacy and students` reading achievement; (2) there is a significant influence between Reading Interest and students` reading achievement; (3) there is a significant influence between Self-efficacy and Reading Interest to students` reading achievement. The population of this study consisted of 857 students of The Eighth grade students of State school in Baturaja Timur Subdistrict namely SMP Negeri 9 OKU, SMP Negeri 13 OKU, SMP Negeri 23 OKU, SMP Negeri 32 OKU and SMP Negeri 34 OKU in academic year 2013/2014. The try-out was done in SMP Negeri 34 OKU with 32 respondents. In this research, the writer used sample size so the writer get size of sample population based on table of sample size, the writer got 343 students at 95% confidence level from 857 students. The researcher took the sample by using simple random sampling. The result showed that (1) there was a significant influence between students’ self-efficacy and reading achievement of the eighth grade students of State Schools in Baturaja Timur Subdistrict, (2) there was a significant influence between students’ reading interest and reading achievement of the eighth grade students of State Schools in Baturaja Timur Subdistrict, (3) there were a significant influence among students’ self-efficacy and reading interest toward reading achievement of the eighth grade students of State Schools in Baturaja Timur Subdistrict. Key Word: Self-efficacy, Reading Interest and Reading Achievement